Role of Superficial CD200 Marker in Differential Diagnosis of Malignant B-Cell Lymphoproliferative Diseases - YuV Mirolyubova; EA Stadnik; TS Nikulina; VV Strugov; TO Andreeva; YuV Virts; RV Grozov; AYu Zaritskey (Клиническая онкогематология)
Background & Aims. Flow cytometry is successfully used for diagnosis of malignant lymphoproliferative disorders. However, there are atypical cases that are difficult to interpret; thus, new markers relevant for the differential diagnosis are to be searched for. The aim is to analyze CD200 expression in patients with B-cell lymphoproliferative disorders.